Aging Adults and Seasonal Influenza: Does the Vitamin D Status (H)Arm the Body? - Pierre Olivier Lang; Dimitrios Samaras (Journal of Aging Research)
Vitamin D (VitD), although originally described as an essential hormone for bone and mineral homeostasis, appears to have an active role in regulating specific facets of human immunity. Indeed, VitD has been shown to have significant effects on cytokine production and lymphocyte proliferation. Evidence that VitD affects clearance of selected pathogens is supported by epidemiological and clinical data, while its coadministration with influenza vaccine in mice enhanced both mucosal and systemic antibody responses. This paper aims to examine how VitD may contribute to limiting the burden of influenza infection in the aging and aged adults, a population in which this burden remains considerable. Furthermore, we discuss how VitD status may play a role in host resistance to influenza virus and influence the immunogenicity of the influenza vaccines currently licensed for adults aged 65 years or over by its effects on innate and adaptive immunities.